2019
DOI: 10.1111/acer.14111
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Combined tDCS Over Right Inferior Frontal Cortex and Cognitive Bias Modification: Null Effects on Drinking and Alcohol Approach Bias

Abstract: Background: Deriving novel treatments for alcohol use disorders (AUDs) is of critical importance, as existing treatments are only modestly effective for reducing drinking. Two promising strategies for treating AUDs include cognitive bias modification (CBM) and transcranial direct current stimulation (tDCS). While each strategy has shown positive results in reducing drinking or alcohol-related constructs (e.g., craving), initial tests of the combination of CBM and tDCS have shown mixed results. The present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…ApBM was shown to modify alcohol avoidance and approach bias (AvB/ApB) in the expected direction in social drinkers (54), hazardous drinkers (HZD) (55), risky drinkers (51), and AUD (26)(27)(28). However, replication of these effects failed in six studies in social (53), heavy (48,50,52,53), hazardous drinkers (49), and AUD (42,46). Loijen et al (43) reported an ApB reduction in AUD but did not test this effect against a control group, thereby limiting the statistical explanatory power.…”
Section: Apbm: Effects On Experimental Tasksmentioning
confidence: 99%
See 2 more Smart Citations
“…ApBM was shown to modify alcohol avoidance and approach bias (AvB/ApB) in the expected direction in social drinkers (54), hazardous drinkers (HZD) (55), risky drinkers (51), and AUD (26)(27)(28). However, replication of these effects failed in six studies in social (53), heavy (48,50,52,53), hazardous drinkers (49), and AUD (42,46). Loijen et al (43) reported an ApB reduction in AUD but did not test this effect against a control group, thereby limiting the statistical explanatory power.…”
Section: Apbm: Effects On Experimental Tasksmentioning
confidence: 99%
“…Additionally, one study did find HD to drink significantly less than controls during a taste test (50). Four studies with hazardous and heavy drinkers observed no effects of ApBM on alcohol consumption at 1-week, 1-month, or 3-month post-intervention (41, 48,49,51).…”
Section: Apbm: Effects On Drinking Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Although we tried to explore various regulatory variables, there are still some possible influencing variables, which are not discussed in this paper, such as tDCS combined with other treatments (cognitive bias modification, emotional regulation). tDCS combined with cognitive bias modification has shown limited effect on treatment outcomes (95)(96)(97). Moreover, emotional regulation can help the curative effects of tDCS (98)(99)(100)(101); after emotion regulation training, using tDCS has better results (100).…”
Section: Influence Of Moderatorsmentioning
confidence: 99%
“…Interestingly, a further study found that tDCS over the left DLPFC significantly decreased the engagement bias toward drug cues in abstinent methamphetamine users (Shahbabaie et al, 2018). Finally, a recent study evaluated the effects of 4 sessions of combined tDCS targeting the right inferior frontal gyrus and cognitive bias modification training in high-risk drinkers (AUDIT score >8) and found no effect on drinking measures or alcohol approach biases (Claus et al, 2019).…”
Section: Combining Cognitive Training/therapy With Nibsmentioning
confidence: 99%